2014
DOI: 10.1021/ef501923f
|View full text |Cite
|
Sign up to set email alerts
|

Coal Pyrolysis for High-Quality Tar and Gas in 100 kg Fixed Bed Enhanced with Internals

Abstract: Using internals in kilogram-laboratory fixed bed pyrolysis of coal has been newly reported to greatly upgrade the pyrolysis performance in terms of the yield and quality of the produced tar and pyrolysis gas. This work is devoted to further verifying such a finding through pyrolysis tests in enlarged fixed bed reactors with and without internals at obviously increased coal treatment capacities of about 100 kg of coal per test. The reactors were electrically heated, and the tests were via batchwise operation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Pyrolysis technology is an emerging technique for producing high‐quality biofuels in liquid, solid, and gaseous phases 4‐9 . The catalytic pyrolysis of coal is an advanced technology applied to cracking the larger tar components into lighter tar components and gases 10‐13 . Previous studies have reported that the tar produced from the catalytic pyrolysis of LRC can be developed into value‐added chemicals, such as benzene, toluene, and xylene (BTX), as well as decalin, tetralin, and naphthalene 14‐18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrolysis technology is an emerging technique for producing high‐quality biofuels in liquid, solid, and gaseous phases 4‐9 . The catalytic pyrolysis of coal is an advanced technology applied to cracking the larger tar components into lighter tar components and gases 10‐13 . Previous studies have reported that the tar produced from the catalytic pyrolysis of LRC can be developed into value‐added chemicals, such as benzene, toluene, and xylene (BTX), as well as decalin, tetralin, and naphthalene 14‐18 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The catalytic pyrolysis of coal is an advanced technology applied to cracking the larger tar components into lighter tar components and gases. [10][11][12][13] Previous studies have reported that the tar produced from the catalytic pyrolysis of LRC can be developed into value-added chemicals, such as benzene, toluene, and xylene (BTX), as well as decalin, tetralin, and naphthalene. [14][15][16][17][18] Wang et al examined the effect of the catalyst (NiW/Al 2 O 3 -USY) for cracking high range aromatics into low range aromatics to obtain a diesel product with a large carbon range.…”
mentioning
confidence: 99%
“…Catalytic cracking is a promising way for obtaining high‐quality tar, and catalyst can cause secondary cracking of coal pyrolysis tar, making heavy components cracked into light oil and gas . Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…Tar fractions were quantified by simulated distillation in GC 7890 (Aglient) according to ASTM D2887‐13 (the Standard Test Method for boiling range distribution of petroleum fractions by gas chromatography). The tar fractions were divided into 2 parts according to two temperature ranges: 50–360 °C; and higher than 360 °C …”
Section: Introductionmentioning
confidence: 99%